1996
DOI: 10.1179/joc.1996.8.4.295
|View full text |Cite
|
Sign up to set email alerts
|

Does Verapamil Help Overcome Multidrug Resistance in Tumor Cell Lines and Cancer Patients?

Abstract: The aim of these experimental and clinical studies was to determine if verapamil helps overcome multidrug resistance in tumor cells and in cancer patients. The effect of the calcium channel blocker verapamil on the antiproliferative activity of epirubicin (Farmorubicin, Farmitalia) was followed up in in vitro studies on two constant human leukemia cell lines: CEM/O (P-gp negative) and CEM/VCR 1000 with a positive multidrug resistant (MDR) phenotype. The MTT assay was used to study the antiproliferative activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 5 publications
0
7
1
Order By: Relevance
“…Verapamil is often used as a P‐gp blocker. In human therapy, verapamil has been used, in association with conventional chemotherapy, in order to reduce the chemoresistance of metastatic breast cancer (Timcheva & Todorov, 1996; Belpomme et al , 2000 ). Since it has been shown that the expression of the Na V 1.5 is associated with lymph node invasion on the one hand, and that, on the other hand, verapamil blocks the Na V 1.5 expressed in breast cancer cells, it will be interesting to determine by which mechanism verapamil exerts its beneficial effect: blockade of the sodium current and/or reversion of the MDR phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Verapamil is often used as a P‐gp blocker. In human therapy, verapamil has been used, in association with conventional chemotherapy, in order to reduce the chemoresistance of metastatic breast cancer (Timcheva & Todorov, 1996; Belpomme et al , 2000 ). Since it has been shown that the expression of the Na V 1.5 is associated with lymph node invasion on the one hand, and that, on the other hand, verapamil blocks the Na V 1.5 expressed in breast cancer cells, it will be interesting to determine by which mechanism verapamil exerts its beneficial effect: blockade of the sodium current and/or reversion of the MDR phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this P‐gp is blocked by molecules such as verapamil and diltiazem ( Cornwell et al , 1987 ). Thus, in some drug‐resistant metastatic cancers, the efficacy of chemotherapy was improved when verapamil was given in association with the usual drugs combination (Timcheva & Todorov, 1996; Belpomme et al , 2000 ).…”
Section: Introductionmentioning
confidence: 99%
“…16 In the early 1980s, it was found that CCBs are inhibitors of MDR in leukemia cells, 17,18 and VER was the first compound to reach clinical trial for its ability to reverse MDR. 16 Though some clinical trials failed due to high toxicity of VER or absence of improvement in the clinical outcome, 19 others showed that VER improves patient survival, [20][21][22][23] including a randomized study of NSCLC. 24 The association between antihypertensive medications and the survival in cancer patients remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Other investigators conducted a study to determine the antitumor effects of calcium channel blocker VER on multidrug resistance in leukemia cells and in breast cancer patients. They noticed that concentrations of VER at 3 μg/mL and 10 μg/mL enhanced the effects of epirubicin (an anthracycline) on leukemia cells with positive multidrug resistance phenotype by 10 and 19 folds respectively in vitro [6,7] .It has been reported that diltiazem, a calcium channel blocker showed synergestic activity with doxorubicin against the growth of Ehrlich ascites carcinoma cells in experimental animals [8] Therefore, the aim of this study is directed to investigate the effect of the calcium channel blocker verapamil (VER) on the anticancer activity of DOX against the growth of human breast cancer cells using sulfarhodamine-B assay. Apoptosis, cell cycle phase distribution, DOX cellular uptake and the activity of multidrug resistant proteins have also been investigated in the presence and absence of Verapamil.…”
Section: Introductionmentioning
confidence: 99%